The Cambridge Aerospace Dictionary - Gunston, Bill (Cambridge Cambridge University Press, 2004)
This dictionary is an essential tool for people who must read and understand technical content regarding the aerospace industry and specific aircraft. An ideal reference for engineering and physics students, it is based on three previous editions of the popular Jane's Aerospace Dictionary by Bill Gunston, OBE, FraeS, one of the most widely read and respected aviation writers of all time. Gunston has added over 15,000 new terms as well as brief explanations of aerospace materials and organizations to this new edition. Terms used in the dictionary reflect the diverse and international nature of the aerospace industry. Bill Gunston is a renowned and prolific aerospace journalist. Currently an editor with Jane's Information Group, he has also served as a technical editor for Flight International and Science Journal and is the author of over 300 books. A former RAF pilot, Gunston's distinguished fifty-year professional career has led to appointments as an Officer of the Order of the British Empire and as a Fellow of the Royal Aeronautical Society.
Includes Appendix.
Keywords: Aeronautics -- Dictionaries